2007
DOI: 10.1021/ef700210q
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Speciation in Petroleum:  Atmospheric Pressure Photoionization or Chemical Derivatization and Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Molecular characterization of sulfur-containing species in petroleum is important because sulfur-containing compounds are detrimental to the environment and the refining processes. In a recent report, the sulfur-containing compounds in a vacuum bottom residue (VBR) were methylated to enhance their detectability by electrospray ionization (ESI) mass analysis. The most abundant sulfur compounds exhibited relatively low double bond equivalents (4 < DBE < 12). Alternatively, atmospheric pressure photoionization (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
185
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(190 citation statements)
references
References 21 publications
2
185
0
Order By: Relevance
“…Furthermore, in case of MeESI, a slow decrease of response factors towards higher DBE values can be projected. Extrapolation of the MeESI response factor versus DBE values (equation in Figure 4c) predicts a response factor close to zero (no methylation occurring) for DBE=24, which is consistent with previous observations [18].…”
Section: Response Factorssupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, in case of MeESI, a slow decrease of response factors towards higher DBE values can be projected. Extrapolation of the MeESI response factor versus DBE values (equation in Figure 4c) predicts a response factor close to zero (no methylation occurring) for DBE=24, which is consistent with previous observations [18].…”
Section: Response Factorssupporting
confidence: 91%
“…For the same purpose, a selective derivatization of the nonpolar sulfur species to methylsulfonium salts prior to their analysis was reported [11] but found to exclude molecules with more than six or seven aromatic rings [18]. In this context, APPI was proposed more suitable for the analysis of compounds with higher aromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that through chemical methylation treatment, thioether, and thiophenic etc. OSCs in crude oil can be ionized for selective oxidation in the Electrospray Ionization (ESI) mode (Müller et al, 2005;Shi et al, 2010aShi et al, , 2010bPan et al, 2010;Liu et al, , 2010bLiu et al, , 2011, or in the Atmospheric Pressure Photo-Ionization (APPI) mode (Purcell et al, 2007;Liu et al, , 2010b in order to conduct FT-ICR MS analysis to characterize their distributions.…”
mentioning
confidence: 99%
“…Purcell et al (2007) further compared the results in the APPI and ESI mode (Purcell et al, 2007) and showed that methylation pretreatment preformed a relatively stronger selectivity on those OSCs with low DBE values and proved incapable on those OSCs with high DBE values. In fact, different ionization method on OSCs analysis cannot have the same results (Panda et al, 2009).…”
mentioning
confidence: 99%
“…Recently, continuous-flow field desorption [14] and lowvoltage electron ionization [15] coupled with FT-ICR MS were reported for the study of VGOs of different origin and of different boiling ranges, respectively. Other reports [16] compared the use of the derivatization method using ESI detection with atmospheric pressure photoionization (APPI) and indicated that the range in the first case mentioned was limited to double bond equivalent (DBE) values below 15 and therefore the APPI approach was favored. It has to be noted here that the chemical derivatization process generates salts which are in fact solution-phase ions that are useful for ESI without further solvent modifiers.…”
Section: Introductionmentioning
confidence: 99%